A Game Development-based strategy for Teaching Software Design Patterns through Challenge-Based Learning under a Flipped Classroom approach - Silveira, Ismar Frango (Anais do Workshop sobre Educação em Computação (WEI), 2016)
Software Design Patterns, namely those belonging to GoF catalog, are gradually being incorporated into undergraduate Computer Sciencesrelated curricula worldwide. However, this is a subject that often requires students to have some maturity on Software Development issues, which is a scenario that is barely found on actual classrooms. Besides, the comprehensive taught of many patterns' aspects depends upon professors' expertise on a large range of Software Engineering and Object Orientation-related topics. Both aspects are possibly caused by the complexity and abstract nature of the subject, whose concrete, real-world applications not always are successfully reached in an undergraduate course. In this sense, this paper presents a strategy for Teaching GoF Design Patterns through a Game Development Process, under a Flipped Classroom pedagogical context. The results of some case studies are also shown, taken from two classes where Challenge-based Learning techniques were applied.